Pengaruh Metode Pembelajaran Role Playing terhadap Kepercayaan Diri Siswa Kelas V dalam Pembelajaran Bahasa Indonesia - Hani Putri Utami; Zahara Hasnah (CV Berkah Syahdin Trust, 2025)
This research was motivated by the low level of students’ self-confidence in learning the Indonesian language. This issue is attributed to the inappropriate and insufficiently varied teaching methods used by the teacher. As a result, students’ self-confidence in Indonesian language learning is categorized as low. Therefore, the researcher was interested in experimenting with the Role Playing learning method to improve the self-confidence of Grade V. This research is quantitative in nature and uses a pre-experimental design with a one-group pretest-posttest model. The population of the study consisted of all Grade V students, totaling 13 students. Data analysis was conducted using the T-test with the help of SPSS version 2023. The data was processed using quantitative methods and then described through hypothesis testing. The results of the study indicate that the Role Playing learning method has an influence on the self-confidence of Grade V students at SDN 18 Balimbiang. The findings from the Paired Samples Test show a significance level (Sig. 2-tailed) of 0.00. Based on degrees of freedom (df = 12) and a significance level of 0.05, the critical t-value is 11.52. Since the calculated t-value (t_count) is greater than the critical t-value (15.689 > 11.52), and Sig. (2-tailed) 0.00 < 0.05, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. It can be concluded that the Role Playing learning method significantly influences the self-confidence of Grade V students in Indonesia language learning.